Historical dictionary of the Great Depression 1929 - 1940 - Olson, James Stuart 1946- (Greenwood Press, 2001)
Publisher description: Today when most Americans think of the Great Depression, they imagine desperate hoboes riding the rails in search of work, unemployed men selling pencils to indifferent crowds, bootleggers hustling illegal booze to secrecy-shrouded speakeasies, FDR smiling, or Judy Garland skipping along the yellow brick road. Hard times have become an abstraction. But there was a time when economic suffering was real, when hunger stalked the land, and Americans tried to forget their troubles in movie theaters or in front of a radio. From the stock market crash of October 1929 to Germany's invasion of Norway, France, and the Low Countries in 1940, the Great Depression blanketed the world economy. Its impact was particularly deep and direct in the United States. This was the era when the federal government became a major player in the national economy and Americans bestowed the responsibility for maintaining full employment and stable prices on Congress and the White House, making the Depression years a major watershed in U.S. history. In more than 500 essays, this book provides a ready reference to those hard times, covering the diplomacy, popular culture, intellectual life, economic problems, public policy issues, and prominent individuals of the era.
Keywords: Geschichte 1929-1940; Wirtschaft; Depressions -- 1929 -- United States -- Dictionaries; Weltwirtschaftskrise -- 1929-1932; USA; United States -- Civilization -- 1918-1945 -- Dictionaries; United States -- Economic conditions -- 1918-1945 -- Dictionaries; United States -- Social conditions -- 1933-1945 -- Dictionaries; Wörterbuch